PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDS AISYIYAH BENGKALIS - Indrawati Indrawati; Lazim. N Lazim. N; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the problem of this research is the weakness of student’s learning result of mathematic subject. It show from 23 student’s, who did not complete reach KKM 15 students (65.21%), while reaching 8 students KKM (34.78%) with the average value of the class is 58.34. KKM predetermined school is 65. According to this problem, the researchers have conducted research using the method of classroom action research by applying Model Cooperative Learning Think Pair Share (TPS). At the first meeting of the first cycle of teacher activity percentage 54.16% with enough categories, at a meeting both increased to 62.5% in both categories. In the second cycle the first meeting with a percentage of 79.16% with a good category and at the second meeting increased to 95.83% with the category very well. Activities of students has increased, in the first cycle of the first meeting of 58.33% with enough categories and the second meeting increased to 66.66% in both categories. While in the first meeting of the second cycle of student increase activity to 75% with good category and the second meeting increased to 91.66% with a good category. The average student learning outcomes before the application is 62.17 increased to 63.91 in the first cycle, and increase 71.65 in the second cycle. While classical completeness in the first cycle and the second cycle is reached. The implementation of cooperative learning model Think Pair Share (TPS) can boost the results of fourth grade students of SDS Aisyiyah Bengkalis in mathematic subject.Key words: Cooperative model type think pair share (TPS), learning result of mathematic